Convergência jornalística e cultura profissional: a experiência do Núcleo Integrado Esportivo da Rede Paraíba de Comunicação - Carneiro, Angélica Gomes de Oliveira Lúcio (2015)
Journalism has always been subject to change due to technological innovations, and two great revolutions in the nineteenth and twentieth centuries are given as milestones in this process: the arrival of the rotary printing press and the mass media in 1850, and the computerization in the 1970s. In contemporary times, the computerization - as part of this second movement - provides new changes in media companies, not only in relation to the management aspect and business strategies, but also with the ways of dealing with the news stories and journalistic practices. The crisis in the media industry leads companies to turn to the reduction of production costs, the professional profile is changed establishing the model, often far from reality, of the "universal journalist", from which is required a diverse editorial capacity, adaptable to any area. We have reached a new field for empirical studies, with the companies sin earch of the journalistic convergence and integrated newsroom, in a reaction to this complex scenario. There are multiple platforms for content distribution, and communication professionals try to adapt to this format. This study examines how cultural aspects configure the adoption of productive routines in the newsroom of the NIE - "Núcleo Integrado Esportivo" (Integrated Sports Core) at Rede Paraíba de Comunicação, a company comprised of radio and television stations, newspaper and news sites, based in João Pessoa, Brazil. We have, as a general goal: mapping the marks of journalistic convergence in the NIE at Rede Paraíba, focusing mainly on the professional dimension. From that, we established the following specific objectives: to get to know the available infrastructure for the work of a multimedia professional; to analyze the perceptions of journalists about the process of journalistic convergence from their work routine; to show which changes occur in the journalistic culture with the implementation of an integrated newsroom and to make a profile of the journalists working in the NIE. Besides the bibliographical research, as methodological approach, we used a combination of quantitative and qualitative methods, with questionnaires, participant observation and in-depth interview. Results indicate that the synergistic step in which the NIE is today is the convergence by three, according to the "media scale" as proposed by Salaverría and Negredo. We also identified the presence of the multitask journalist and some phases of the "dynamic model of convergence", notably cross-promotion, content cloning and multiplatform distribution. The creation of an integrated production core altered the productive routines of journalists, but it can be seen that the full establishment of the convergence culture is still a long way to go.